Uma investigação sobre o desenvolvimento da escrita em aulas de ciências no quinto ano do ensino fundamental - Nunes, Maria Betânia Tenório (2012)
The study characterizes the written record of a group of students from the 5th grade of primary classes in Brazil, in investigative science and its contribution to the development of writing. We analyze the interactions occurring during classes as well as students' written production. We examine how this process was linked with acquisition of writing and identify the resources used by students to communicate their observations, hypotheses and conclusions. The methodological design takes as a parameter an ethnographic approach, with systematic monitoring of science classes for a semester in addition to recording audio and video lessons planned with an investigative strategy. Was performed microanalysis of events occurring during the classes and analyzed the texts of students based on content analysis. The results indicate that change in the dynamics used in science classes, favored the use of writing structures that had not been explored by the participant group. In investigative classes analyzed in this study, the students could express their ideas, from what they had experienced with the experiments, with opportunities to use advanced cognitive abilities, being necessary to reorganize thought to express the new knowledge.